2015
DOI: 10.1016/j.adolescence.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Children's online coping strategies: Rethinking coping typologies in a risk‐specific approach

Abstract: Understanding how children deal with problematic situations online is helpful in developing efficient awareness raising and online resilience building initiatives. In this article, we will discuss and develop typologies for online coping strategies. In a school survey, 2046 Flemish children aged 10-16 were asked about how they (would) respond when confronted with different types of online risks. Using principal component analyses and multi-dimensional scaling, we identified different types of cross-risk and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
11
0
4
Order By: Relevance
“…Of the 13 studies included in the review, five did not include resilience as a part of their analyses (Cross et al, 2016; Livingstone & Görzig, 2014; Nielsen et al, 2015; Rodelli et al, 2018; Vandoninck & d’Haenens, 2015). Instead, the authors of some studies offered resilience-based interpretations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 studies included in the review, five did not include resilience as a part of their analyses (Cross et al, 2016; Livingstone & Görzig, 2014; Nielsen et al, 2015; Rodelli et al, 2018; Vandoninck & d’Haenens, 2015). Instead, the authors of some studies offered resilience-based interpretations.…”
Section: Resultsmentioning
confidence: 99%
“…Rodelli et al (2018) assessed healthy lifestyles associated with resilience and found that healthier behaviors were associated with less suicidal ideation. An active coping style, such as seeking help or used safety tools such as blocking and reporting, reduced harm (Vandoninck & d’Haenens, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Online coping can be described as "Internet-specific problem-solving strategies children adopt after a negative experience online" (Vandoninck et al, 2013). Some youths cope more effectively with online adversities than others and are hence more resilient to harm from online risks (Livingstone et al, 2011;Smahel & Wright, 2014;Staksrud & Livingstone, 2009;Vandoninck & d'Haenens, 2015;Vandoninck et al, 2013). Research has shown that youths that have more difficulties coping with offline risks also have more difficulties coping with online risks (Vandoninck, d'Haenens, & Segers, 2012).…”
Section: Online Resiliencementioning
confidence: 99%
“…Přínosem dalších autorů (Vandoninck & dʼHaenens, 2015) k výzkumu specifik on-line copingových strategií v kontextu kyberšikany ve věku 10-16 let je upozornění na potenciálně odlišný pohled na strategie Pasivita -Lhostejnost-Vyhýbání v souvislosti s potencionálním rozfázováním nebo kombinací těchto strategií.…”
Section: Poznatky Současných Výzkumů Copingových Strategií U Dětí Mlaunclassified
“…Z hlediska genderových nálezů copingových strategií u dětí a dospívajících s normální tělesnou hmotností jsou odlišnosti potvrzovány různě silně a v závislosti na akademickém nebo jiném kontextu (Ben -Eliyahu & Kaplan, 2015;Čanigová, 2001;Eschenbeck, Schmid, Schröder, Wasserfall, & Kohlmann, 2018). U on -line strategií jsou genderové odlišnosti diferencovány v souvislosti s obsahovými riziky nebo s věkem dětí (Vandoninck & dʼHaenens, 2015).…”
Section: Poznatky Současných Výzkumů Copingových Strategií U Dětí Mlaunclassified